2011
DOI: 10.5824/1309-1581.2011.1.002x
|View full text |Cite
|
Sign up to set email alerts
|

Yeni Ağ Teknolojileri Bağlamında Yeni İletişim Ortamları ve Bilgi

Abstract: This paper, examines new media and information in the context of new network technologies. In terms of communication researchers, new communication technologies and media are interesting. Because they are digital, interactive, hypertextual, virtual, on the network. New media provides some opportunities such as content production, political participation and awareness. This, also, can be associated with decreasing number of audience in the media other than internet. When new media and knowledge economy are exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…NES was defined more than half a century ago and was included in a psychiatric diagnosis system for the first time with the publication of DSM-5 (de Zwaan et al, 2014; Köroğlu, 2013b). There are publications in the literature reporting that NES frequently accompanies mental disorders, is most commonly associated with depression and is also associated with impulsivity (Atasoy et al, 2014; Sevincer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NES was defined more than half a century ago and was included in a psychiatric diagnosis system for the first time with the publication of DSM-5 (de Zwaan et al, 2014; Köroğlu, 2013b). There are publications in the literature reporting that NES frequently accompanies mental disorders, is most commonly associated with depression and is also associated with impulsivity (Atasoy et al, 2014; Sevincer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ADHD is often associated with other psychiatric disorders that contribute to the functional impairment of ADHD patients (Cortese et al, 2008). Some reports have suggested that not only are eating disorders and obesity common in ADHD but also ADHD symptoms are also common in patients with obesity and eating disorders (Tarakçıoğlu & Aksoy, 2018).Anorexia nervosa, bulimia nervosa, binge eating disorder, and night eating syndrome (NES) are among the main eating disorders included in the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders) (Köroğlu, 2013b). Impaired eating attitudes, on the other hand, are problematic eating behaviors that are seen as a risk factor for eating disorders but with symptoms that do not meet the diagnosis of eating disorders (Levin & Rawana, 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations